Endophytic Fungi Fusarium Equiseti EF2 Isolated from Leucas Aspera: A Novel Biocontrol Agent Against Culex Sp: Life Sciences-Microbiology - Kavitha, Kuppuswamy; Aarthi, Paneerselvam; Prakash, Mani (International Journal of Life Science and Pharma Research, 2022)
Among several life-threatening diseases, vector-borne diseases play a significant role. Mosquito-borne conditions are dangerous and are more prevalent. Culex is the most prevalent and causative agent of many zoonotic diseases among various mosquito species. Endophytic fungi that reside in the healthy plant produce an array of bioactive compounds against several conditions causing pathogens. Thus, this study aimed to identify a novel antilarval combination from the endophytic fungi present in Leucas aspera leaves. The objectives include the isolation of endophytic fungi from leaf samples, selection of potent antilarval endophyte, and characterization of its bioactive compound. The exploration of the least studied fungi, Fusarium equiseti as an endophyte in the leaves of Leucas aspera with potent antilarval properties is an inquisitive discovery. A total of 10 endophytic fungi (EF-1 to EF-10) were isolated and screened for the larvicidal activity of the fungal broth and its spore. The best isolate, EF-2 was identified as Fusarium equiseti. The crude sample and the active fraction of the ethyl acetate extract exhibited potent antilarval properties against Culex mosquito larvae with 90% mortality. Phytochemical analysis and characterization studies by UV-Vis spectroscopy and GC-MS revealed bioactive compounds in the active fraction of the extract. Overall, this study suggested a new option for biocide formulation that could aid in the effort to control mosquitoes. Among several discoveries of bioactive compounds from the plant extracts, this study has identified novel compounds from its endophytic fungi rather than the plant itself. The extracts of endophytic fungi Fusarium equiseti isolated from Leucas aspera, has antilarvicidal activity.